[ECO]systems of resilience practices : contributions for sustainability and climate change adaptation - Colucci, Angela; Pesaro, Giulia (Elsevier, 2022)
"Ecosystems of Resilience Practices: Contributions for Sustainability and Climate Change Adaptation focuses on resilience in action by exploring and providing approaches, perspectives, toolboxes, and theoretical discourses for the improvement and enhancement of territorial and community resilience practices towards sustainability and climate change mitigation/adaptation. The book develops a set of tools and design criteria to support the dissemination of resilience practices. This new toolset will support the expansion and reinforcement of resilience practices and the building of solutions related to climate change."--